1 - The Challenges of Feminism: Gender, Ethics and Responsible Academic Freedom in African Universities - Amina Mama, (Journal of Higher Education in Africa, 2011)
Feminist theory and ethics have enormous potentials to transform and ener- gize the discourse on academic freedom and social responsibility. As a theory of knowledge and an intellectual practice, feminism deconstructs the episte- mological foundations of patriarchy and contributes to the emancipation of women as subjects and studies on and about women as critical intellectual engagements. Despite this potential, the discourse on academic freedom and intellectual responsibility in African universities has rarely yielded ground for feminist ethics, and feminist intellectuals within the universities have had to struggle for space. This article discusses these struggles to insert feminism as part of the intellectual discourse on academic freedom within Africa’s scholarly community between 1990 – the year of the Aca- demic Freedom Conference in Kampala – and 2010. The institutional and intellectual challenges that have been encountered by feminist-inspired aca- demics are highlighted. Finally, the author discusses the imperatives to move the discourse on gender in African scholarly communities beyond the nor- mative policy rhetoric to tackling the gendered configuration of academic institutions.